The ratio of the interzygomatic width with mesiodistal width of maxillary anterior teeth - Savabi O; Ghasabzadeh M (Tehran University of Medical Sciences, 2002)
Esthetics is one of the prosthetic treatment goals. Correct selection of anterior teeth, regarding size and appearance, results in a successful treatment. The goal of the present research was to investigate the relationship between interzygomatic width and maxillary anterior teeth width in order to find a better determinant for artificial anterior teeth selection. In this study, the interzygomatic width and maxillary central incisors width and also the width of six maxillary anterior- teeth, in 71 subjects (29females and 42 males) were measured. The results showed a significant difference in maxillary anterior teeth width, comparing men and women, (P<0.05). These measurement in people under study, are less than Europeans. The interzygomatic width was also more in men than women (PO.05), which is, less than of European race. The ratio between interzygomatic and central maxillary incisor width was 15:1 which is less than 16:1 that is used in clinic. Thus, it is recommended to pay more attention to anterior teeth selection, especially in young patients.